English Speaking Material Development for Hospitality Students at A Vocational High School in Palangka Raya - Givency, Christy; Fauzan, Akhmad; Misrita (IKIP Siliwangi, 2026)
To meet the increasing demand for skilled human resources in the hospitality industry, English-speaking skills are essential for effective workplace communication. At SMK Negeri 3 Palangka Raya, a lack of English for Specific Purposes (ESP) materials tailored to the learning needs of eleventh-grade Hospitality Program students has led to difficulties in speaking proficiency. The study aimed to develop English-speaking materials specifically designed for the hospitality field. Using a Research and Development (R&D) approach guided by the ADDIE model and TPACK framework, data were collected through questionnaires, interviews, and document analysis. In addition, the materials were informed by relevant learning theories to address students’ needs. The resulting handbook features thematic hospitality dialogues, peer discussion sections, lesson recaps, audio listening practice, vocabulary and pronunciation exercises, multiple-choice comprehension questions, and roleplay-based speaking activities. Expert validations rated the handbook as “Very Feasible,” while student feedback indicated positive engagement, increased speaking confidence, and improved communicative competence. The findings suggest that the handbook bridges the gap between a general English textbook and the practical workplace needs, offering a more interactive and profession-oriented learning experience. Broader classroom application, long-term trials, and multimodal enhancements are recommended for further development.